2016
DOI: 10.1515/revneuro-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-receptor protein tyrosine kinases in the excitotoxicity induced by the overactivation of NMDA receptors

Abstract: AbstractProtein tyrosine phosphorylation is one of the primary modes of regulation of N-methyl-d-aspartate (NMDA) receptors. The non-receptor tyrosine kinases are one of the two types of protein tyrosine kinases that are involved in this process. The overactivation of NMDA receptors is a primary reason for neuron death following cerebral ischemia. Many studies have illustrated the important role of non-receptor tyrosine kinases in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In addition, oxidative stress and the formation of oxygen free radicals are key components of the glutamate-induced neurotoxicity, a pathogenetic mechanism that has received much attention as a critical player in ALS development and progression [ 32 ]. Several lines of evidence reported that src family protein tyrosine kinases are involved in excitotoxicity [ 16 19 ], pointing to a possible role in the pathogenesis of ALS. Accordingly, we report the activation of two members of the src family kinases highly expressed in the central nervous system, src and fyn, both in the cortex and in the spinal cord of SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oxidative stress and the formation of oxygen free radicals are key components of the glutamate-induced neurotoxicity, a pathogenetic mechanism that has received much attention as a critical player in ALS development and progression [ 32 ]. Several lines of evidence reported that src family protein tyrosine kinases are involved in excitotoxicity [ 16 19 ], pointing to a possible role in the pathogenesis of ALS. Accordingly, we report the activation of two members of the src family kinases highly expressed in the central nervous system, src and fyn, both in the cortex and in the spinal cord of SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence reported that src family protein tyrosine kinases are involved in excitotoxicity [ 16 19 ], pointing to their possible role in the pathogenesis of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…The NMDA receptor, Src, and pannexin 1 (Panx1) comprise a metabotropic signaling complex that is involved in the process of cerebral ischemia ( Li et al, 2021 ). Src indirectly associates with NMDA receptors by interacting with NADH dehydrogenase subunit 2 (ND2) via amino acids 40–80 ( Gingrich et al, 2004 ; Liu et al, 2008 ; Sun et al, 2016 ). Src is anchored to NMDA receptors through the interaction between the PDZ3 domain of PSD-95 and the SH2 domain of Src ( Kalia and Salter, 2003 ; Sun et al, 2016 ).…”
Section: Signaling Molecules Mediating Metabotropic Nmda Receptor Sig...mentioning
confidence: 99%
“…Src indirectly associates with NMDA receptors by interacting with NADH dehydrogenase subunit 2 (ND2) via amino acids 40–80 ( Gingrich et al, 2004 ; Liu et al, 2008 ; Sun et al, 2016 ). Src is anchored to NMDA receptors through the interaction between the PDZ3 domain of PSD-95 and the SH2 domain of Src ( Kalia and Salter, 2003 ; Sun et al, 2016 ). Panx1 interacts with Src via the amino acid sequence 305–318 at the C terminus ( Weilinger et al, 2012 ).…”
Section: Signaling Molecules Mediating Metabotropic Nmda Receptor Sig...mentioning
confidence: 99%
“…Phosphorylation of GluN2B after cerebral ischemia may enhance its function and aggravate ischemic brain injury (Sun et al, 2016). After recruited to GluN2B C-terminal, CaMKIIα phosphorylated GluN2B at Ser1303 and up-regulated GluN2B function (Ahmed et al, 2017).…”
Section: Roles Of Iglurs In Cerebral Ischemiamentioning
confidence: 99%